2016
DOI: 10.1007/s10072-016-2609-7
|View full text |Cite
|
Sign up to set email alerts
|

Understanding walking activity in multiple sclerosis: step count, walking intensity and uninterrupted walking activity duration related to degree of disability

Abstract: In multiple sclerosis (MS), physical activity (PA) is most commonly measured as number of steps, while also walking intensity and walking activity duration are keys for a healthy lifestyle. The aim of this study was to investigate (1) the number of steps persons with MS (PwMS) take; (2) the number of steps they take at low and moderate intensity; and (3) their walking activity duration for 2, 3, 6, 10, 12 and 14 uninterrupted minutes; all related to the degree of disability. 64 PwMS participated, distinguished… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
14
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 43 publications
8
14
1
Order By: Relevance
“…While significant increases in short and long clinical gait tests after MIR are important results, the primary goal of motor rehabilitation in pwMS is to increase everyday life mobility of pwMS, possibly also leading to improved participation and HRQoL. Using accelerometry as an objective and reliable outcome measure of real-life mobility in the present cohort [2227], the number of steps performed per day as a marker of real life mobility was found to be comparable to previous studies with pwMS with “mild” walking disability averaging significantly more steps than those with “moderate and severe” walking disability [17,18]. We could demonstrate that an intervention of twenty-eight days of MIR resulted indeed not only in a significant better performance in walking capacity tests, but also in an overall increase in everyday life mobility, a finding that has not been reported so far.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…While significant increases in short and long clinical gait tests after MIR are important results, the primary goal of motor rehabilitation in pwMS is to increase everyday life mobility of pwMS, possibly also leading to improved participation and HRQoL. Using accelerometry as an objective and reliable outcome measure of real-life mobility in the present cohort [2227], the number of steps performed per day as a marker of real life mobility was found to be comparable to previous studies with pwMS with “mild” walking disability averaging significantly more steps than those with “moderate and severe” walking disability [17,18]. We could demonstrate that an intervention of twenty-eight days of MIR resulted indeed not only in a significant better performance in walking capacity tests, but also in an overall increase in everyday life mobility, a finding that has not been reported so far.…”
Section: Discussionsupporting
confidence: 77%
“…However the ecological validity of these walking-specific measurements, that is the extent to which changes in these tests can be generalized to everyday life, has recently been questioned. Concerns arise from the observation that uninterrupted walking over 2 or 6 minutes is very uncommon in daily lives of pwMS thereby challenging its real life relevance [16,17]. In addition, short and long walking tests mainly sample walking capacity in an artificial setting instead of real-life walking performance of pwMS, which is further reflected by the T25FW, 2MWT and 6MWT correlating only weakly with everyday life walking reported in cross-sectional studies [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Past studies addressing the daily number of steps in pwMS are inconsistent with conflicting results even in patients on a similar level of disability, presumably because different tracking devices were used. This led to a wide range of documented average step counts, starting from 5,903 ± 3,185 up to 10,243 ± 3,817 steps per day among fully ambulatory pwMS [25,26]. In our study cohort we observed an average step count (6,863 ± 2,592) at the lower end of the range described above.…”
Section: Plos Onesupporting
confidence: 59%
“…Past studies addressing the daily number of steps in pwMS are inconsistent with conflicting results even in patients on a similar level of disability, presumably because different tracking devices were used. This led to a wide range of documented average step counts, starting from 5,903 ± 3,185 up to 10,243 ± 3,817 steps per day among fully ambulatory pwMS (21,22). In our study cohort we observed an average step count (6,863 ± 2,592) at the lower end of the range described above.…”
Section: Discussionsupporting
confidence: 59%